2011
DOI: 10.1088/0004-637x/739/2/69
|View full text |Cite
|
Sign up to set email alerts
|

OUTFLOWS FROM ACTIVE GALACTIC NUCLEI: KINEMATICS OF THE NARROW-LINE AND CORONAL-LINE REGIONS IN SEYFERT GALAXIES,

Abstract: As part of an extensive study of the physical properties of active galactic nuclei (AGN) we report high spatial resolution near-IR integral-field spectroscopy of the 1 Based on observations at the European Southern Observatory VLT (60.A-9235, 070.B-0649, 070.B-0664, 074.B-9012, 075.B-0040, 076.B-0098 and 083.B-0332).2 Based on observations at the W. M. Keck Observatory, which is operated as a scientific partnership among the California Institute of Technology, the University of California and the National Aero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
361
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(423 citation statements)
references
References 140 publications
(197 reference statements)
44
361
11
1
Order By: Relevance
“…Although our sources do have extended lower surfacebrightness line emission with more quiescent kinematics, their contribution to the integrated line profile is smaller, and this gas is outside the region where a connection with the radio source is obvious (Villar-Martín et al 2003). In quasars and Seyfert galaxies at low redshift, Husemann et al (2013) and Müller-Sánchez et al (2011) also find that the gas is only perturbed near the radio source, in broad agreement with our findings (but see Liu et al 2013). …”
Section: Comparison With Other Massive High-z Galaxiessupporting
confidence: 88%
“…Although our sources do have extended lower surfacebrightness line emission with more quiescent kinematics, their contribution to the integrated line profile is smaller, and this gas is outside the region where a connection with the radio source is obvious (Villar-Martín et al 2003). In quasars and Seyfert galaxies at low redshift, Husemann et al (2013) and Müller-Sánchez et al (2011) also find that the gas is only perturbed near the radio source, in broad agreement with our findings (but see Liu et al 2013). …”
Section: Comparison With Other Massive High-z Galaxiessupporting
confidence: 88%
“…Müller Sánchez et al (2006) argue that coronal line emission stems from the inner NLR and that they are probably associated with outflows. Recently, Müller-Sánchez et al (2011) and Mazzalay et al (2013a) observed extended emission in the coronal lines of NGC 1068, as well as a great complexity in the morphology and kinematics. This indicates that the nature of coronal line emission is far from being understood.…”
Section: Emission-line Fitsmentioning
confidence: 99%
“…However, a significant fraction of early-type massive galaxies have a substantial amount of warm neutral and cold molecular gas Crocker et al 2012;Serra et al 2012;Bayet et al 2013), so simple energy arguments may not be enough. To inhibit star formation and efficient AGN fueling, many observational studies of AGN feedback have focused on outflows (Fischer et al 2010;Feruglio et al 2010;Dasyra & Combes 2012;Müller-Sánchez et al 2011;Sturm et al 2011;Combes et al 2013;Labiano et al 2013;Alatalo et al 2014c;Morganti et al 2013a;Mahony et al 2013;McNamara et al 2014). Spectroscopic observations of ionized, neutral, and molecular gas suggest that winds are ubiquitous in galaxies hosting AGN (e.g., Morganti et al 2005b;Lehnert et al 2011;Dasyra & Combes 2011;Alatalo et al 2011;Guillard et al 2012;Cicone et al 2014;Förster Schreiber et al 2014).…”
Section: Introductionmentioning
confidence: 99%